A fiber-reinforced functional gradient layered ceramic matrix composite material and a preparation method and device thereof

Through the preparation method of fiber-reinforced functional gradient layered ceramic matrix composite material, the problems of low efficiency, high cost and no obvious difference in the preparation process of existing ceramic matrix composite materials are solved, and the lightweight, cost reduction and performance improvement of the material are achieved.

CN118908731BActive Publication Date: 2025-04-04HARBIN INST OF TECH AT WEIHAI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410971582.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-19
Publication Date
2025-04-04
Estimated Expiration
2044-07-19

AI Technical Summary

Technical Problem

The preparation process of existing ceramic matrix composite materials has problems such as low efficiency, high cost and high weight, and the material structure is a gradient homogeneous structure without a gradient, and there is no obvious difference in performance.

Method used

The preparation method of fiber-reinforced functional gradient layered ceramic-based composite material is adopted, and the outer dense layer and inner loose layer are formed by preparing water-based ceramic slurry, freeze-drying, impregnation and cracking, and hot pressing treatment, and the outer dense layer are formed to optimize the ceramic content and density distribution.

Benefits of technology

It has achieved lightweight, cost reduction and performance improvement of ceramic matrix composite materials. The outer dense layer has excellent ablation resistance, the inner loose layer meets heat protection needs, the material density increases, and the preparation cycle is shortened.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118908731B_ABST
    Figure CN118908731B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of ceramic-based composite materials, and specifically to a fiber-reinforced functional gradient layered ceramic-based composite material and a preparation method and device thereof, comprising the following steps: preparing a fiber preform, preparing a water-based ceramic slurry, impregnating the water-based ceramic slurry into the fiber preform, then freeze-drying, repeatedly performing 3 to 6 times of impregnation and cracking under a protective atmosphere, and then placing it in a hot press furnace for hot pressing treatment, and finally obtaining a fiber-reinforced functional gradient layered ceramic-based composite material, the functional gradient layered fiber ceramic-reinforced ceramic-based composite material comprising an outer dense layer and an inner loose layer. The present application can quickly achieve densification through the mixed use of slurry process, freeze drying method, impregnation and cracking method, and hot pressing assisted multiple processes. At the same time, the preparation cycle is shortened and the cost is also reduced. At the same time, the functional gradient layered fiber ceramic-reinforced ceramic-based composite material has excellent ablation resistance and is light in weight while meeting the heat protection requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic-based composite materials, and in particular to a fiber-reinforced functional gradient layered ceramic-based composite material and a preparation method and device thereof. Background Art

[0002] Continuous fiber reinforced composite materials have the characteristics of low density, high specific strength, high specific modulus, high temperature resistance, oxidation resistance, good reliability, etc., and are the development direction of high-performance aviation engine materials. Among them, ceramic matrix composite materials are a kind of high temperature (1650℃) and low density (2.5g / cm 3 ~3.3g / cm 3 ) structural materials, which are expected to replace the density greater than 8.0g / cm 3 Nickel-based or single-crystal nickel alloys are used as the engine's combustion chamber, flame stabilizer, inner cone, tail nozzle, worm gear outer ring, high-pressure turbine, low-pressure turbine and other components.

[0003] At present, the commonly used processes for preparing ceramic matrix composite materials include chemical vapor deposition (CVI), impregnation pyrolysis (PIP), reactive melt infiltration (RMI) and slurry impregnation. A single preparation process often has various disadvantages, such as low efficiency of chemical vapor deposition, easy surface sealing, multiple rounds of high temperature pyrolysis, great damage to fabric performance, high reactive melt infiltration temperature, severe erosion of fibers by refractory metals, and difficulty in effective penetration of fabrics by slurry impregnation, and serious hollow shell phenomenon. Multiple process combinations can effectively improve the disadvantages of a single process, such as a mixed process of chemical vapor deposition and impregnation pyrolysis, which fully utilizes the advantages of fast densification rate in the early stage of the reaction of CVI process and PIP process, and the preparation cycle of the process is shortened by about 50% compared with a single PIP process or CVI process, but the price of the precursor solution is high, the cost of multiple rounds of impregnation pyrolysis process is high, the preparation cycle still requires at least 1 month, and the prepared ceramic matrix composite material is heavy and costly; a mixed process of impregnation pyrolysis and reactive melt infiltration shortens the preparation cycle and controls the content of the ceramic phase, and the composite material has low porosity, high mechanical properties and high thermal conductivity. However, in order to make the raw materials reach a molten state and effectively penetrate, the heat treatment temperature is relatively high, which causes a certain degree of damage to the fiber, the coating uniformity is difficult to control, the product thermal conductivity is high, the cost of multiple rounds of PIP process is high, and the prepared composite material is too heavy. At the same time, the continuous fiber reinforced composite material currently used is a non-gradient homogeneous structure, the difference in the ceramic phase content of the inner and outer layers is small, there is no obvious difference in performance, and the overall weight is relatively large.

[0004] Therefore, it is necessary to further improve the structure, manufacturing method and device of the current ceramic-based composite materials. Summary of the invention

[0005] The purpose of the present application is to provide a fiber-reinforced functional gradient layered ceramic matrix composite material and a preparation method and device thereof.

[0006] The embodiments of the present application can be implemented through the following technical solutions:

[0007] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0008] Step 100, preparing a fiber preform;

[0009] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate as a dispersant and deionized water as a solvent, adding ceramic powder in proportion and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed, adjusting the pH value of the slurry with ammonia water, and then sequentially performing ball milling and vacuum degassing to finally obtain a water-based ceramic slurry;

[0010] Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank 1, wherein the filled part is the outer dense layer, and the unfilled part is the inner loose layer;

[0011] Step 400, freeze drying, freeze-curing the composite body 1 in a freeze drying device, demolding the composite body 1 after curing, drying, sublimating and high-temperature sintering the demolded composite body 1, and cooling the composite body 1 to room temperature to obtain a composite body 2;

[0012] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution, and then placed in a vacuum sintering furnace for high-temperature cracking, and the impregnation and high-temperature cracking process steps are repeated 3 to 6 times under a protective atmosphere to finally obtain a composite body 3;

[0013] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace for hot pressing treatment, and finally obtaining a fiber-reinforced functional gradient layered ceramic matrix composite material.

[0014] Furthermore, in step 100, the raw material for making the fiber preform is any one of carbon fiber, oxide fiber, nitride fiber, and silicon carbide fiber.

[0015] Further, in step 200, the ceramic powder matrix is ​​any one or a combination of SiC, ZrB2, TiB2, HfB2, SiBCN, SiBON, and hafnium-based;

[0016] Furthermore, in step 200, the mass proportion of ammonium polyacrylate is 0.5-1.5wt%, the volume ratio of the ceramic powder is 1:1-4:1, the initial solid content of the slurry obtained after uniform mixing is 20-50vol.%, and the adjusted pH value range is 8.5-9.5;

[0017] Furthermore, during the ball milling process, the ball-to-material ratio is 1:1-1.5:1, the ball mill speed is 60-80 r / min, the ball milling time is 15-20 h, and the ball milling is carried out by alternating forward rotation for 10-15 min and reverse rotation for 10-15 min.

[0018] Furthermore, in step 300, the thickness of the outer dense layer of the composite material green body 1 finally generated is 1 / 5 to 1 / 2 of the total thickness of the composite material green body 1.

[0019] Further, in step 400, during freezing and solidification, the freezing temperature is -40 to -20°C, and the freezing time is 24 to 36 hours;

[0020] Furthermore, during the drying and sublimation process, the drying and sublimation time is 30 to 40 hours;

[0021] Furthermore, during the sintering process, first, at 350-450°C, the temperature is kept at 0.5-1h to discharge the organic additives; secondly, the temperature is raised to 1200-1400°C for sintering and kept at 1.5-2h; finally, the temperature is lowered to 150-200°C at a cooling rate of 2-3°C / min, and cooled to room temperature to obtain a fiber preform II.

[0022] Furthermore, in step 400, the thickness of the outer dense layer of the second fiber preform accounts for 1 / 5 to 1 / 2 of the total thickness of the second fiber preform, and the ceramic content is 20 to 50 vol.%.

[0023] Further, in step 500, the precursor solution is any one of a diboride precursor, a silicon carbide precursor or a silicon boron nitrogen precursor;

[0024] Further, the pressure of immersion in the precursor solution is 4-9 MPa, the immersion temperature is 45-60° C., and the solid content of the precursor solution is 30-50%;

[0025] Furthermore, the ceramicization heating rate in the vacuum sintering furnace is 4 to 10°C / min, and the pyrolysis temperature is 1000 to 1500°C;

[0026] Furthermore, the protective atmosphere is any one of argon and helium;

[0027] Furthermore, in step 500, the ceramic content of the outer dense layer of the composite body 3 is 50-80 vol.%, and the ceramic content of the inner loose layer is 20-30 vol.%.

[0028] Further, in step 600, during the hot pressing treatment, the temperature is 1000-1500°C, the heating rate is 1-2°C / min, the pressure is 10-50MPa, and the heat preservation is finally performed for 0.5-1h;

[0029] The thickness of the fiber-reinforced functional gradient layered ceramic matrix composite material is 1 / 4 to 1 / 2 of the thickness of the fiber preform.

[0030] A fiber-reinforced functional gradient layered ceramic matrix composite material, the fiber-reinforced functional gradient layered ceramic matrix composite material is prepared using the fiber-reinforced functional gradient layered ceramic matrix composite material preparation method, the thickness of the fiber-reinforced functional gradient layered ceramic matrix composite material is 1 / 4 to 1 / 2 of the thickness of the fiber preform, the fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, the ceramic content of the outer dense layer is 60 to 90 vol.%, and the ceramic content of the inner loose layer is 30 to 40 vol.%.

[0031] A device for preparing a fiber-reinforced functional gradient layered ceramic-based composite material comprises a storage device, a freeze-drying device, a connecting pipe and a valve. The storage device is connected to the freeze-drying device via the connecting pipe. The connecting pipe is provided with a valve for controlling the opening and closing of the connecting pipe channel. The freeze-drying device is provided with a mold for placing the fiber preform.

[0032] The fiber-reinforced functional gradient layered ceramic matrix composite material and its preparation method and device provided in the embodiments of the present application have at least the following beneficial effects:

[0033] 1. In the present application, the water-based ceramic slurry is quantitatively infiltrated and filled into the fiber preform by the slurry process, and the water-based ceramic slurry is freeze-dried by the freeze-drying process. The water-based ceramic slurry is directly in contact with the cold end plane at the bottom of the fiber preform. The freezing medium at the bottom of the water-based ceramic slurry begins to nucleate and crystallize preferentially due to its proximity to the cold source, and grows directionally from bottom to top along the temperature gradient. At the same time, the pore structure in the composite body is randomly oriented and distributed in a gradient, forming an outer dense layer, and the precursor solution is impregnated under a certain pressure to make the internal gas The pores are opened, so that the subsequent impregnation can be carried out effectively, and the impregnation cycle is shortened, the material density is increased, and the inner loose layer is filled. After hot pressing, the internal pores, especially the pores between the fiber bundles, are mostly compacted and disappear, so that the material can be relieved by toughening mechanisms such as debonding and bridging when bearing loads, further reducing the number of impregnation cracking times, quickly achieving densification, greatly shortening the preparation cycle, reducing costs, and effectively increasing the ceramic content, so that the outer dense layer with excellent ablation resistance and the inner loose layer with a lighter weight that meets the heat protection requirements can be quickly prepared;

[0034] 2. The fiber-reinforced functional gradient layered ceramic matrix composite material in this application not only meets the heat protection performance requirements of the outer dense layer of the material, but also achieves lightweight products due to the low weight of the internal loose layer, and the cost is also reduced, which can further meet the urgent needs of industrial production for lightweight and rapid preparation of high-performance fiber-reinforced ceramic matrix composite materials;

[0035] 3. The fiber-reinforced functional gradient layered ceramic matrix composite material prepared in this application is mainly used in the direction of high-performance aviation engine materials. At the same time, due to its light weight and the layered structure that can greatly improve the impact resistance of the material, it can greatly reduce the weight of aviation engine materials. The lightweight structure can bring a series of benefits, such as increasing the payload, increasing the flight range or range, reducing losses, and protecting the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a process flow chart of the preparation method of the fiber-reinforced functional gradient layered ceramic matrix composite material in this application;

[0037] Figure 2 C of Example 1 in this application f / SEM image of ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites;

[0038] Figure 3 C of Example 1 in this application f / SEM image of the outer dense layer of ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composite;

[0039] Figure 4 C of Example 1 in this applicationf / SEM image of the fracture of the outer dense layer of ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composite;

[0040] Figure 5 A diagram of a device for preparing a fiber-reinforced functionally gradient layered ceramic matrix composite material in this application;

[0041] Figure 6 This is a reference diagram for the preparation process of the fiber-reinforced functionally gradient layered ceramic matrix composite material in this application.

[0042] The numbers in the figure are: 1-valve, 2-storage device, 3-connecting pipe, 4-mold, 5-freeze drying device. DETAILED DESCRIPTION

[0043] Hereinafter, the present application will be further described based on preferred embodiments with reference to the accompanying drawings.

[0044] In addition, various components on the drawings are enlarged (thickened) or reduced (thinned) for ease of understanding, but this practice is not intended to limit the scope of protection of the present application.

[0045] Words importing the singular also include the plural and vice versa.

[0046] In the description of the embodiments of the present application, it should be noted that if the terms "upper", "lower", "inside", "outside", etc. indicate an orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship in which the products of the embodiments of the present application are usually placed when in use, it is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, in the description of the present application, in order to distinguish different units, the words first, second, etc. are used in this specification, but these are not limited by the order of manufacture, nor can they be understood as indicating or implying relative importance, and their names may be different in the detailed description and claims of the present application.

[0047] The vocabulary in this specification is used to illustrate the embodiments of the present application, but is not intended to limit the present application. It should also be noted that, unless otherwise clearly specified and limited, the terms "disposed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, a direct connection, an indirect connection through an intermediate medium, or a connection between the two elements. For those skilled in the art, the specific meanings of the above terms in this application can be specifically understood.

[0048] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material, such as Figure 1 As shown, the following steps are included:

[0049] Step 100: prepare a fiber preform, wherein the fiber preform is made of any one of carbon fiber, oxide fiber, nitride fiber and silicon carbide fiber.

[0050] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 0.5 to 1.5 wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 1:1 to 4:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 20 to 50 vol.%, adjusting the pH value of the slurry to 8.5 to 9.5 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1:1 to 1.5:1, the ball mill speed is 60 to 80 r / min, the ball milling time is 15 to 20 h, and the ball milling method is used to alternately rotate forward for 10 to 15 min and reverse for 10 to 15 min. Finally, vacuum degassing is performed to obtain a water-based ceramic slurry;

[0051] Furthermore, the ceramic powder matrix is ​​any one or a combination of SiC, ZrB2, TiB2, HfB2, SiBCN, SiBON, and hafnium-based.

[0052] Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank one, wherein the filled part is an outer dense layer, and the unfilled part is an inner loose layer, wherein the thickness of the outer dense layer is 1 / 5 to 1 / 2 of the total thickness of the composite material blank one.

[0053] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -40 to -20°C, the freezing time is 24 to 36 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 30 to 40 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 350 to 450°C, the temperature is kept for 0.5 to 1 hour to discharge the organic additives; secondly, the temperature is raised to 1200 to 1400°C for sintering, and the temperature is kept for 1.5 to 2 hours; finally, the temperature is lowered to 150 to 200°C, the cooling rate is 2 to 3°C / min, and after cooling to room temperature, a composite material blank 2 is obtained, the thickness of the outer dense layer accounts for 1 / 5 to 1 / 2 of the total thickness of the fiber preform 2 and the ceramic content is 20 to 50 vol.%.

[0054] Step 500, impregnation and cracking, firstly, the composite body 2 is placed in a precursor solution with a solid content of 30-50% under the conditions of a pressure of 4-9 MPa and an impregnation temperature of 45-60° C., and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 4-10° C. / min and a cracking temperature of 1000-1500° C., and the impregnation and high-temperature cracking process steps are repeated 3-6 times under the protective atmosphere of argon or helium, and finally a composite body 3 with a ceramic content of 50-80 vol.% in the outer dense layer and 20-30 vol.% in the inner loose layer is obtained;

[0055] Further, the solution is any one of a diboride precursor, a silicon carbide precursor or a silicon boron nitrogen precursor;

[0056] Step 600, hot pressing treatment, placing the composite material blank three in a hot pressing furnace, hot pressing treatment is performed under the conditions of a temperature of 1000-1500°C, a heating rate of 1-2°C / min, and a pressure of 10-50MPa, and finally keeping the temperature for 0.5-1h to finally obtain a fiber-reinforced functional gradient layered ceramic matrix composite material.

[0057] Furthermore, the thickness of the fiber-reinforced functional gradient layered ceramic matrix composite material is 1 / 4 to 1 / 2 of the thickness of the fiber preform.

[0058] A fiber-reinforced functionally gradient layered ceramic matrix composite, such as Figure 6 As shown, the fiber-reinforced functional gradient layered ceramic matrix composite material is prepared by the above-mentioned fiber-reinforced functional gradient layered ceramic matrix composite material preparation method, the thickness of the fiber-reinforced functional gradient layered ceramic matrix composite material is 1 / 4 to 1 / 2 of the thickness of the fiber preform, and the fiber-reinforced functional gradient layered ceramic matrix composite material includes an outer dense layer and an inner loose layer, the ceramic content of the outer dense layer is 60 to 90 vol.%, and the ceramic content of the inner loose layer is 30 to 40 vol.%. The density of the outer dense layer is 3.5 to 4.2 g / cm 3 The density of the inner loose layer is 1.8~2.08g / cm 3 The outer layer has strong ablation resistance, and the operating temperature reaches 2000℃, and the inner layer also reaches above 1500℃. The outer dense layer of the generated fiber-reinforced functional gradient layered ceramic-based composite material has excellent heat protection performance, and the inner loose layer has low cost and light weight.

[0059] The present application also provides a device for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material, such as Figure 5As shown, it includes a storage device 2, a freeze drying device 5, a connecting pipe 3 and a valve 1. The fiber-reinforced functional gradient layered ceramic matrix composite material is prepared by the cooperation of the storage device 2 and the freeze drying device 5, wherein the storage device 2 is connected to the freeze drying device 5 through the connecting pipe 3, and the connecting pipe 3 is provided with a valve 1, and the valve 1 is used to control the passage of the water-based ceramic slurry. At the same time, a mold 4 is provided in the freeze drying device 5, and the mold 4 is used to place the fiber preform and the bottom of the mold 4 is connected to the connecting pipe 3. When in use, firstly place the water-based ceramic slurry in the storage device 2, place the fiber preform in the mold 4, pump the freeze drying device 5 to a vacuum state, open the valve 1, and use the pressure difference between the storage device 2 and the freeze drying device 5 to uniformly and slowly fill the water-based ceramic slurry into the fiber preform through the connecting pipe 3. When it is filled to a certain thickness, a composite material blank is obtained.

[0060] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material is provided in the present application, wherein the preparation of the fiber-reinforced functional gradient layered ceramic matrix composite material is achieved through freeze drying, multiple impregnation cracking and hot pressing. The freeze drying process of the composite body can not only obtain a high-density body, but also ensure that the interface layer does not crack before the composite body is densified and subjected to high-temperature heat treatment, thereby forming a weak interface between the fiber and the composite body, and finally achieving the effect of strengthening and toughening the composite body.

[0061] The freeze drying method is based on the principle of pressure reduction and boiling point reduction. As long as the pressure is below the triple point pressure, the water in the material can be sublimated directly from water to water vapor without passing through the liquid phase. According to this principle, the wet raw material can be first frozen below the freezing point to turn the water in the raw material into solid ice, and then the ice can be directly converted into steam and removed under an appropriate vacuum environment, and then the water vapor can be condensed by a water vapor condenser in the vacuum system to dry the material. This method of obtaining dryness by vacuum freezing is a process of physical state change and movement of water. This process occurs at low temperature and low pressure. Therefore, the basic principle of freeze drying is the mechanism of heat and mass transfer at low temperature and low pressure. In the present application, after the water-based ceramic slurry is placed into the fiber preform by pressure, the water-based ceramic slurry directly contacts the cold end plane at the bottom of the fiber preform. The freezing medium at the bottom of the water-based ceramic slurry begins to nucleate and crystallize preferentially due to its proximity to the cold source, and grows in a directional manner from bottom to top along the temperature gradient. During the freezing and solidification process, as the distance between the freezing medium and the cold source in the water-based ceramic slurry increases, the supercooling inside the water-based ceramic slurry decreases, and the growth rate of the freezing front slows down, which ultimately makes the pore structure orientation in the composite material blank random and gradient distributed. Freeze drying is different from ordinary heating drying. The water in the material basically sublimates on the solid surface below 0°C, and the material itself remains in the ice shelf when frozen. Therefore, the volume of the dried product remains unchanged, and it is loose and porous, achieving precise control of the depth of the fiber fabric surface and preparing a high-density layer.

[0062] The impregnation pyrolysis method is to change the raw materials of ultra-high temperature ceramic components from powder to precursor polymers of corresponding components, introduce the precursor solution with good wetting effect into the fiber braid through pressure impregnation, and directly convert it into ultra-high temperature ceramic components inside the braid after solidification-pyrolysis. Through the impregnation process, the matrix filling of the loose layer is achieved, which can promote high-density sintering on the one hand, and on the other hand, the pores produced by pyrolysis can effectively reduce the thermal conductivity. Since the precursor polymer will produce a certain volume shrinkage after solidification-pyrolysis, in theory, the material needs to undergo several repeated impregnation-curing-pyrolysis processes.

[0063] During the preparation of ceramics by the precursor method, the impregnation densification process is slow, and the porosity of the product is large and the pore distribution is uneven. Therefore, the hot pressing process is introduced into the traditional atmospheric pressure impregnation cracking process. The basic principle of the hot pressing method is to make a blank with a sinterable matrix raw material powder and reinforcing fibers, and sinter them under high temperature. The matrix material is sintered and combined with the reinforcing fibers to form a ceramic matrix composite material.

[0064] During the cracking process of the precursor into ceramic, on the one hand, small molecular cracking gas will be produced, leaving a large number of pores inside the product; on the other hand, due to the change in density, the volume of the precursor will shrink during the cracking process, and a large porosity will also be produced. The fiber bundles inside the three-dimensional fiber braid are crisscrossed, and after the precursor solution is impregnated and cracked, narrow channels and even hard shells will be formed, making the subsequent impregnation process difficult. It is difficult for the precursor solution to reach the internal pores. After several cycles, the internal pores will form closed pores, which will be preserved until the end of the preparation cycle, forming a material with a large porosity. If no pressure is applied, the defects of the interface will remain, and the densification of the material will be more difficult. After the material is placed in a hot pressing furnace for hot pressing treatment, the thickness of the material is compressed to 1 / 4 to 1 / 2 of the original thickness, and most of the internal pores, especially the pores between the fiber bundles, are compacted and disappear, so that the material can be relieved by toughening mechanisms such as debonding and bridging when bearing loads. Therefore, the density of the inner and outer layers of the material is greatly improved, and the ceramic content of the inner and outer layers is also greatly improved. Finally, the ceramic content of the outer dense layer of the material is 60 to 90 vol.%, and the ceramic content of the inner loose layer is 30 to 40 vol.%. The surface of the outer dense layer is sintered and densified, and at the same time, a strong connection is formed between the particles of the inner loose layer, further improving the strength of the fabric.

[0065] The water-based ceramic slurry is quantitatively infiltrated and filled into the fiber preform by a slurry process, and the water-based ceramic slurry is freeze-dried by a freeze-drying process to form an outer dense layer. The precursor solution is impregnated under a certain pressure to open the internal pores and enable subsequent impregnation to be carried out effectively. The impregnation cycle is shortened, the material density is increased, and the inner loose layer is filled. After hot pressing treatment, the number of impregnation cracking times can be reduced, densification can be achieved quickly, the preparation cycle can be greatly shortened, the cost can be reduced, and the ceramic content can be effectively increased. An outer dense layer with excellent ablation resistance and an inner loose layer with a lighter weight that meets heat protection requirements can be quickly prepared.

[0066] Embodiment 1

[0067] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0068] Step 100: prepare a fiber preform, wherein the fiber preform is made of carbon fiber.

[0069] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 0.5wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 1:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 20vol.%, adjusting the pH value of the slurry to 8.5 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1:1, the ball mill speed is 60r / min, the ball milling time is 15h, and the ball milling method is used to alternately rotate forward for 10min and reverse for 10min. Finally, vacuum degassing is performed to obtain ZrB2-SiC water-based ceramic slurry;

[0070] Furthermore, the ceramic powder matrix is ​​ZrB2-SiC.

[0071] Step 300, impregnating the fiber preform, placing the ZrB2-SiC water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the ZrB2-SiC water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank one, wherein the filled part is an outer dense layer, and the unfilled part is an inner loose layer, wherein the thickness of the outer dense layer is 1 / 5 of the total thickness of the composite material blank one.

[0072] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -40°C, the freezing time is 24 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 30 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 350°C, the temperature is kept for 0.5 hours to discharge the organic additives; secondly, the temperature is raised to 1200°C for sintering, and the temperature is kept for 1.5 hours; finally, the temperature is lowered to 150°C, the cooling rate is 2°C / min, and after cooling to room temperature, a composite material blank 2 is obtained in which the thickness of the outer dense layer accounts for 1 / 5 of the total thickness of the fiber preform 2 and the ceramic content is 20 vol.%.

[0073] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution with a solid content of 30% under the conditions of a pressure of 4 MPa and an impregnation temperature of 45°C, and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 4°C / min and a cracking temperature of 1000°C, and the impregnation and high-temperature cracking process steps are repeated 3 times under the protective atmosphere of argon gas, and finally a composite body 3 with a ceramic content of 50 vol.% in the outer dense layer and 20 vol.% in the inner loose layer is obtained;

[0074] Further, the precursor solution is a silicon carbide precursor, i.e., polycarbosilane;

[0075] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace, hot pressing treatment under the conditions of a temperature of 1000°C, a heating rate of 1°C / min, and a pressure of 10 MPa, and finally keeping the temperature for 0.5 h, finally obtaining C f / ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites.

[0076] Furthermore, the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 4 of the thickness of the fiber preform.

[0077] A C f / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composites, the C f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material is prepared using the above-mentioned fiber-reinforced functional gradient layered ceramic matrix composite material preparation method, wherein the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 4 of the thickness of the fiber preform. f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, wherein the ceramic content of the outer dense layer is 60 vol.%, and the density is 3.5 g / cm 3 The ceramic content of the inner loose layer is 28 vol.%, and the density is 1.8 g / cm 3 The outer layer has strong ablation resistance, the operating temperature reaches 2000℃, and the inner layer operating temperature also reaches above 1500℃.

[0078] like Figure 2 As shown, C f The micromorphology at the interface of the ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite is divided into two layers, the upper layer is the outer dense layer, the lower layer is the inner loose layer, and the direction of the fiber is perpendicular to the thickness direction of the material; Figure 3 C f SEM image of the outer dense layer of the / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material. The dark circular area is the carbon fiber, the dark circle in the enlarged area in the box is the carbon fiber, and the white area is the dispersed ZrB2-SiC ceramic matrix. Figure 4 C fSEM image of the fracture of the outer dense layer of the / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material. The black area is the ZrB2 phase, the gray area is the SiC phase, and the gray-white circular area is the carbon fiber.

[0079] Embodiment 2

[0080] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0081] Step 100: prepare a fiber preform, wherein the fiber preform is made of carbon fiber.

[0082] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 1.5wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 4:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 50vol.%, adjusting the pH value of the slurry to 9.5 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1.5:1, the ball mill speed is 80r / min, the ball milling time is 20h, and the ball milling method is used to alternately rotate forward for 15min and reverse for 15min. Finally, vacuum degassing is performed to obtain ZrB2-SiC water-based ceramic slurry;

[0083] Furthermore, the ceramic powder matrix is ​​ZrB2-SiC.

[0084] Step 300, impregnating the fiber preform, placing the ZrB2-SiC water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the ZrB2-SiC water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank one, wherein the filled part is an outer dense layer, and the unfilled part is an inner loose layer, wherein the thickness of the outer dense layer is 1 / 2 of the total thickness of the composite material blank one.

[0085] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -20°C, the freezing time is 36 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 40 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 450°C, the temperature is kept for 1 hour to remove the organic additives; secondly, the temperature is increased to 1400°C for sintering, and the temperature is kept for 2 hours; finally, the temperature is reduced to 200°C, the cooling rate is 3°C / min, and after cooling to room temperature, a composite material blank 2 with an outer dense layer thickness of 1 / 2 of the total thickness of the fiber preform 2 and a ceramic content of 40 vol.% is obtained.

[0086] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution with a solid content of 50% under the conditions of a pressure of 9 MPa and an impregnation temperature of 60°C, and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 10°C / min and a cracking temperature of 1500°C, and the impregnation and high-temperature cracking process steps are repeated 6 times under the protective atmosphere of argon gas, and finally a composite body 3 with a ceramic content of 70 vol.% in the outer dense layer and 25 vol.% in the inner loose layer is obtained;

[0087] Further, the precursor solution is a silicon carbide precursor, i.e., polycarbosilane;

[0088] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace, hot pressing treatment under the conditions of a temperature of 1500°C, a heating rate of 2°C / min, and a pressure of 50MPa, and finally keeping the temperature for 1h, finally obtaining C f / ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites.

[0089] Furthermore, the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 2 of the thickness of the fiber preform.

[0090] A C f / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composites, the C f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material is prepared using the above-mentioned fiber-reinforced functional gradient layered ceramic matrix composite material preparation method, wherein the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 2 of the thickness of the fiber preform. f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, wherein the ceramic content of the outer dense layer is 75 vol.%, and the density is 4 g / cm 3 The ceramic content of the inner loose layer is 32 vol.%, and the density is 1.9 g / cm 3 The outer layer has strong ablation resistance, the operating temperature reaches 2000℃, and the inner layer operating temperature also reaches above 1500℃.

[0091] Embodiment 3

[0092] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0093] Step 100: prepare a fiber preform, wherein the fiber preform is made of carbon fiber.

[0094] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 1wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 4:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 30vol.%, adjusting the pH value of the slurry to 9 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1.5:1, the ball mill speed is 80r / min, the ball milling time is 20h, and the ball milling method is used to alternately rotate forward for 15min and reverse for 15min. Finally, vacuum degassing is performed to obtain a ZrB2-SiC water-based ceramic slurry;

[0095] Furthermore, the ceramic powder matrix is ​​ZrB2-SiC.

[0096] Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank, such as Figure 6 As shown, the filled part is the outer dense layer, and the unfilled part is the inner loose layer, wherein the thickness of the outer dense layer is 1 / 3 of the total thickness of the composite material blank.

[0097] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -20°C, the freezing time is 24 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 30 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 450°C, the temperature is kept for 1 hour to remove the organic additives; secondly, the temperature is increased to 1300°C for sintering, and the temperature is kept for 1.5 hours; finally, the temperature is reduced to 200°C, the cooling rate is 2°C / min, and after cooling to room temperature, a composite material blank 2 with an outer dense layer thickness of 1 / 3 of the total thickness of the fiber preform 2 and a ceramic content of 50 vol.% is obtained.

[0098] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution with a solid content of 50% under the conditions of a pressure of 8 MPa and an impregnation temperature of 55°C, and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 5°C / min and a cracking temperature of 1500°C, and the impregnation and high-temperature cracking process steps are repeated 4 times under the protective atmosphere of argon gas, and finally a composite body 3 with a ceramic content of 80 vol.% in the outer dense layer and 30 vol.% in the inner loose layer is obtained;

[0099] Further, the precursor solution is a silicon carbide precursor, i.e., polycarbosilane;

[0100] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace, hot pressing treatment under the conditions of a temperature of 1500°C, a heating rate of 2°C / min, and a pressure of 45MPa, and finally keeping the temperature for 1h, finally obtaining C f / ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites.

[0101] Furthermore, the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 3 of the thickness of the fiber preform.

[0102] A C f / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composites, the C f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material is prepared using the above-mentioned fiber-reinforced functional gradient layered ceramic matrix composite material preparation method, wherein the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 3 of the thickness of the fiber preform. f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, wherein the ceramic content of the outer dense layer is 90 vol.%, and the density is 4.2 g / cm 3 The ceramic content of the inner loose layer is 40 vol.%, and the density is 2.08 g / cm 3 The outer layer has strong ablation resistance, the operating temperature reaches 2000℃, and the inner layer operating temperature also reaches above 1500℃.

[0103] Embodiment 4

[0104] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0105] Step 100: prepare a fiber preform, wherein the fiber preform is made of carbon fiber.

[0106] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 0.8wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 4:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 40vol.%, adjusting the pH value of the slurry to 9 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1.5:1, the ball mill speed is 70r / min, the ball milling time is 18h, and the ball milling method is used to alternately rotate forward for 13min and reverse for 13min. Finally, vacuum degassing is performed to obtain ZrB2-SiC water-based ceramic slurry;

[0107] Furthermore, the ceramic powder matrix is ​​ZrB2-SiC.

[0108] Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank one, wherein the filled part is an outer dense layer, and the unfilled part is an inner loose layer, wherein the thickness of the outer dense layer is 1 / 4 of the total thickness of the composite material blank one.

[0109] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -30°C, the freezing time is 30 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 35 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 400°C, the temperature is kept for 1 hour to remove the organic additives; secondly, the temperature is increased to 1250°C for sintering, and the temperature is kept for 2 hours; finally, the temperature is reduced to 180°C, the cooling rate is 2.5°C / min, and after cooling to room temperature, a composite material blank 2 with an outer dense layer thickness of 1 / 4 of the total thickness of the fiber preform 2 and a ceramic content of 42 vol.% is obtained.

[0110] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution with a solid content of 40% under the conditions of a pressure of 8 MPa and an impregnation temperature of 50°C, and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 7°C / min and a cracking temperature of 1300°C, and the impregnation and high-temperature cracking process steps are repeated 5 times under the protective atmosphere of argon gas, and finally a composite body 3 with a ceramic content of 72 vol.% in the outer dense layer and 26 vol.% in the inner loose layer is obtained;

[0111] Further, the precursor solution is a silicon carbide precursor, i.e., polycarbosilane;

[0112] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace, hot pressing treatment under the conditions of a temperature of 1300°C, a heating rate of 1.5°C / min, and a pressure of 46MPa, and finally keeping the temperature for 0.5h, finally obtaining C f / ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites.

[0113] Furthermore, the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 2 / 5 of the thickness of the fiber preform.

[0114] A C f / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composites, the C f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material is prepared using the above-mentioned fiber-reinforced functional gradient layered ceramic matrix composite material preparation method, wherein the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 2 / 5 of the thickness of the fiber preform. f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, wherein the ceramic content of the outer dense layer is 82 vol.%, and the density is 3.8 g / cm 3 The ceramic content of the inner loose layer is 35 vol.%, and the density is 1.95 / cm 3 The outer layer has strong ablation resistance, the operating temperature reaches 2000℃, and the inner layer operating temperature also reaches above 1500℃.

[0115] Embodiment 5

[0116] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0117] Step 100: prepare a fiber preform, wherein the fiber preform is made of carbon fiber.

[0118] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 0.7wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 4:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 35vol.%, adjusting the pH value of the slurry to 9 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1.5:1, the ball mill speed is 75r / min, the ball milling time is 16h, and the ball milling method is used to alternately rotate forward for 14min and reverse for 14min. Finally, vacuum degassing is performed to obtain a ZrB2-SiC water-based ceramic slurry;

[0119] Furthermore, the ceramic powder matrix is ​​ZrB2-SiC.

[0120] Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank one, wherein the filled part is an outer dense layer, and the unfilled part is an inner loose layer, wherein the thickness of the outer dense layer is 1 / 4 of the total thickness of the composite material blank one.

[0121] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -30°C, the freezing time is 30 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 35 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 400°C, the temperature is kept for 1 hour to remove the organic additives; secondly, the temperature is increased to 1250°C for sintering, and the temperature is kept for 2 hours; finally, the temperature is reduced to 180°C, the cooling rate is 2.8°C / min, and after cooling to room temperature, a composite material blank 2 with an outer dense layer thickness of 1 / 4 of the total thickness of the fiber preform 2 and a ceramic content of 38 vol.% is obtained.

[0122] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution with a solid content of 40% under the conditions of a pressure of 8 MPa and an impregnation temperature of 58° C., and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 6° C. / min and a cracking temperature of 1400° C., and the impregnation and high-temperature cracking process steps are repeated 4 times under the protective atmosphere of argon gas, and finally a composite body 3 with a ceramic content of 68 vol.% in the outer dense layer and 27 vol.% in the inner loose layer is obtained;

[0123] Further, the precursor solution is a silicon carbide precursor, i.e., polycarbosilane;

[0124] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace, hot pressing treatment under the conditions of a temperature of 1400°C, a heating rate of 1.5°C / min, and a pressure of 44MPa, and finally keeping the temperature for 0.5h, finally obtaining C f / ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites.

[0125] Furthermore, the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 2 / 5 of the thickness of the fiber preform.

[0126] A C f / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composites, the C f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material is prepared using the above-mentioned fiber-reinforced functional gradient layered ceramic matrix composite material preparation method, wherein the C f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 2 / 5 of the thickness of the fiber preform. f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, wherein the ceramic content of the outer dense layer is 78 vol.%, and the density is 3.7 g / cm 3 The ceramic content of the inner loose layer is 34 vol.%, and the density is 1.93 g / cm 3 The outer layer has strong ablation resistance, the operating temperature reaches 2000℃, and the inner layer operating temperature also reaches above 1500℃.

[0127] Embodiment 6

[0128] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0129] Step 100: prepare a fiber preform, wherein the fiber preform is made of silicon carbide fiber.

[0130] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 0.55wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 3:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 40vol.%, adjusting the pH value of the slurry to 8.5 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1:1, the ball mill speed is 70r / min, the ball milling time is 15h, and the ball milling method is used to alternately rotate forward for 13min and reverse for 13min. Finally, vacuum degassing is performed to obtain SiC water-based ceramic slurry;

[0131] Furthermore, the ceramic powder matrix is ​​SiC.

[0132] Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank one, wherein the filled part is an outer dense layer, and the unfilled part is an inner loose layer, wherein the thickness of the outer dense layer is 1 / 5 of the total thickness of the composite material blank one.

[0133] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -40°C, the freezing time is 24 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 30 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 350°C, the temperature is kept for 0.5 hours to discharge the organic additives; secondly, the temperature is raised to 1200°C for sintering, and the temperature is kept for 1.5 hours; finally, the temperature is lowered to 150°C, the cooling rate is 2°C / min, and after cooling to room temperature, a composite material blank 2 is obtained in which the thickness of the outer dense layer accounts for 1 / 5 of the total thickness of the fiber preform 2 and the ceramic content is 22 vol.%.

[0134] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution with a solid content of 40% under the conditions of a pressure of 5 MPa and an impregnation temperature of 45°C, and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 5°C / min and a cracking temperature of 1000°C, and the impregnation and high-temperature cracking process steps are repeated 5 times under the protective atmosphere of helium, and finally a composite body 3 with a ceramic content of 55 vol.% in the outer dense layer and 22 vol.% in the inner loose layer is obtained;

[0135] Further, the precursor solution is a diboride precursor, i.e., polyzirconium boride;

[0136] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace, hot pressing treatment under the conditions of a temperature of 1000°C, a heating rate of 1°C / min, and a pressure of 12 MPa, and finally keeping the temperature for 0.5 h, finally obtaining SiC f / ZrB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites.

[0137] Furthermore, the SiC f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 4 of the thickness of the fiber preform.

[0138] A SiC f / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composites, the SiC f / ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is prepared using the above-mentioned fiber reinforced functional gradient layered ceramic matrix composite material preparation method, the SiC f The thickness of the ZrB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 4 of the thickness of the fiber preform. f The ZrB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, wherein the ceramic content of the outer dense layer is 74 vol.%, and the density is 3.7 g / cm 3 The ceramic content of the inner loose layer is 30 vol.%, and the density is 1.88 g / cm 3 The outer layer has strong ablation resistance, the operating temperature reaches 2000℃, and the inner layer operating temperature also reaches above 1500℃.

[0139] Embodiment 7

[0140] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0141] Step 100: prepare a fiber preform, wherein the fiber preform is made of silicon nitride fiber.

[0142] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 1.5wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 4:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 50vol.%, adjusting the pH value of the slurry to 9.5 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1.5:1, the ball mill speed is 80r / min, the ball milling time is 20h, and the ball milling method is used to alternately rotate forward for 15min and reverse for 15min. Finally, vacuum degassing is performed to obtain HfB2-SiC water-based ceramic slurry;

[0143] Furthermore, the ceramic powder matrix is ​​HfB2-SiC.

[0144] Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank one, wherein the filled part is an outer dense layer, and the unfilled part is an inner loose layer, wherein the thickness of the outer dense layer is 1 / 2 of the total thickness of the composite material blank one.

[0145] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -20°C, the freezing time is 36 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 40 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 450°C, the temperature is kept for 1 hour to remove the organic additives; secondly, the temperature is increased to 1400°C for sintering, and the temperature is kept for 2 hours; finally, the temperature is reduced to 200°C, the cooling rate is 2.5°C / min, and after cooling to room temperature, a composite material blank 2 with an outer dense layer thickness of 1 / 2 of the total thickness of the fiber preform 2 and a ceramic content of 36 vol.% is obtained.

[0146] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution with a solid content of 50% under the conditions of a pressure of 8.5 MPa and an impregnation temperature of 60° C., and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 10° C. / min and a cracking temperature of 1450° C., and the impregnation and high-temperature cracking process steps are repeated 3 times under the protective atmosphere of helium, and finally a composite body 3 with a ceramic content of 68 vol.% in the outer dense layer and 27 vol.% in the inner loose layer is obtained;

[0147] Further, the precursor solution is a silicon carbide precursor, i.e., polycarbosilane;

[0148] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace, hot pressing treatment under the conditions of a temperature of 1500°C, a heating rate of 2°C / min, and a pressure of 48MPa, and finally keeping the temperature for 1h, finally obtaining SiN f / HfB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites.

[0149] Furthermore, the SiN f The thickness of the HfB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 2 / 7 of the thickness of the fiber preform.

[0150] A SiN f / HfB2-SiC fiber reinforced functional gradient layered ceramic matrix composites, the SiN f / HfB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is prepared using the above-mentioned fiber reinforced functional gradient layered ceramic matrix composite material preparation method, the SiN f The thickness of the HfB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 2 / 7 of the thickness of the fiber preform. f The HfB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, wherein the ceramic content of the outer dense layer is 74 vol.%, and the density is 4.1 g / cm 3 The ceramic content of the inner loose layer is 33 vol.%, and the density is 1.91 g / cm 3 The outer layer has strong ablation resistance, the operating temperature reaches 2000℃, and the inner layer operating temperature also reaches above 1500℃.

[0151] Embodiment 8

[0152] A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material comprises the following steps:

[0153] Step 100: prepare a fiber preform, wherein the fiber preform is made of carbon fiber.

[0154] Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate with a mass proportion of 1wt% as a dispersant and deionized water as a solvent, adding ceramic powder in a volume ratio of 4:1 and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed and the initial solid content is 35vol.%, adjusting the pH value of the slurry to 9.3 with ammonia water, and then ball-milling the slurry. During the ball-milling treatment, the ball-to-material ratio is 1.5:1, the ball mill speed is 80r / min, the ball milling time is 18h, and the ball milling method is used to alternately rotate forward for 15min and reverse for 15min. Finally, vacuum degassing is performed to obtain TiB2-SiC water-based ceramic slurry;

[0155] Furthermore, the ceramic powder matrix is ​​TiB2-SiC.

[0156] Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank one, wherein the filled part is an outer dense layer, and the unfilled part is an inner loose layer, wherein the thickness of the outer dense layer is 1 / 3 of the total thickness of the composite material blank one.

[0157] Step 400, freeze drying, freeze-curing the composite material blank 1 in a freeze drying device, the freezing temperature is -20°C, the freezing time is 24 hours, the composite material blank 1 is quickly demolded after curing, the demolded composite material blank 1 is dried and sublimated in a freeze dryer, after 30 hours of drying and sublimation, the composite material blank 1 is sintered, first, at 450°C, the temperature is kept for 1 hour to remove the organic additives; secondly, the temperature is increased to 1300°C for sintering, and the temperature is kept for 1.5 hours; finally, the temperature is reduced to 200°C, the cooling rate is 2°C / min, and after cooling to room temperature, a composite material blank 2 with an outer dense layer thickness of 1 / 3 of the total thickness of the fiber preform 2 and a ceramic content of 49 vol.% is obtained.

[0158] Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution with a solid content of 50% under the conditions of a pressure of 8 MPa and an impregnation temperature of 55°C, and after impregnation, it is placed in a vacuum sintering furnace, and high-temperature cracking is performed under the conditions of a ceramic heating rate of 5°C / min and a cracking temperature of 1350°C, and the impregnation and high-temperature cracking process steps are repeated 5 times under the protective atmosphere of helium, and finally a composite body 3 with a ceramic content of 76 vol.% in the outer dense layer and 30 vol.% in the inner loose layer is obtained;

[0159] Further, the precursor solution is a diboride precursor, i.e., polytitanium boride;

[0160] Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace, hot pressing treatment under the conditions of a temperature of 1500°C, a heating rate of 2°C / min, and a pressure of 42MPa, and finally keeping the temperature for 1h, finally obtaining C f / TiB2-SiC fiber reinforced functionally gradient layered ceramic matrix composites.

[0161] Furthermore, the C f The thickness of the TiB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 3 of the thickness of the fiber preform.

[0162] A C f / TiB2-SiC fiber reinforced functional gradient layered ceramic matrix composites, the C f The TiB2-SiC fiber-reinforced functional gradient layered ceramic matrix composite material is prepared using the above-mentioned fiber-reinforced functional gradient layered ceramic matrix composite material preparation method, wherein the C f The thickness of the TiB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material is 1 / 3 of the thickness of the fiber preform. f / TiB2-SiC fiber reinforced functional gradient layered ceramic matrix composite material includes an outer dense layer and an inner loose layer, wherein the ceramic content of the outer dense layer is 86 vol.%, and the density is 4.18 g / cm 3 The ceramic content of the inner loose layer is 39 vol.%, and the density is 2.04 g / cm 3 The outer layer has strong ablation resistance, the operating temperature reaches 2000℃, and the inner layer operating temperature also reaches above 1500℃.

[0163] The above is a detailed introduction to the specific implementation methods of the present application. For those skilled in the art, several improvements and modifications may be made to the present application without departing from the principles of the present application. These improvements and modifications also fall within the scope of protection of the claims of the present application.

Claims

1. A method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material, characterized in that: The following steps are involved: Step 100, preparing a fiber preform; Step 200, preparing a water-based ceramic slurry, using ammonium polyacrylate as a dispersant and deionized water as a solvent, adding ceramic powder in proportion and mixing evenly to obtain a slurry in which the ceramic powder is evenly dispersed, adjusting the pH value of the slurry with ammonia water, and then sequentially performing ball milling and vacuum degassing to finally obtain a water-based ceramic slurry; Step 300, impregnating the fiber preform, placing the water-based ceramic slurry in a storage device, placing the fiber preform in a freeze-drying device and evacuating it to a vacuum state, and using the pressure difference to evenly and slowly fill the water-based ceramic slurry in the storage device into the fiber preform, and finally obtaining a composite material blank 1, wherein the filled part is the outer dense layer, and the unfilled part is the inner loose layer; Step 400, freeze drying, freeze-curing the composite body 1 in a freeze drying device, demolding the composite body 1 after curing, drying, sublimating and high-temperature sintering the demolded composite body 1, and cooling the composite body 1 to room temperature to obtain a composite body 2; Step 500, impregnation and cracking, firstly, the composite body 2 is impregnated in a precursor solution, and then placed in a vacuum sintering furnace for high-temperature cracking, and the impregnation and high-temperature cracking process steps are repeated 3 to 6 times under a protective atmosphere to finally obtain a composite body 3; Step 600, hot pressing treatment, placing the composite material blank in a hot pressing furnace for hot pressing treatment, and finally obtaining a fiber-reinforced functional gradient layered ceramic matrix composite material.

2. The method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material according to claim 1, characterized in that: In step 100, the raw material for making the fiber preform is any one of carbon fiber, oxide fiber, nitride fiber, and silicon carbide fiber.

3. The method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material according to claim 1, characterized in that: In step 200, the ceramic powder matrix is ​​any one or a combination of SiC, ZrB2, TiB2, HfB2, SiBCN, SiBON, and hafnium-based; In step 200, the initial solid content of the slurry in which the ceramic powder is evenly dispersed is 20 to 50 vol.%, and the pH value is adjusted to be in the range of 8.5 to 9.5; During ball milling, the ball-to-material ratio is 1:1~1.5:1, the ball mill speed is 60~80 r / min, the ball milling time is 15~20h, and the ball milling is carried out by alternating forward rotation for 10~15 min and reverse rotation for 10~15 min.

4. The method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material according to claim 1, characterized in that: In step 300, the thickness of the outer dense layer of the composite material green body 1 finally generated is 1 / 5 to 1 / 2 of the total thickness of the composite material green body 1.

5. The method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material according to claim 1, characterized in that: In step 400, during freezing and solidification, the freezing temperature is -40 to -20°C and the freezing time is 24 to 36 hours; In the case of drying and sublimation treatment, the drying and sublimation time is 30~40h; During the sintering treatment, first, at 350-450°C, keep the temperature for 0.5-1h to discharge the organic additives; secondly, heat to 1200-1400°C for sintering and keep the temperature for 1.5-2h; finally, cool to 150-200°C at a cooling rate of 2-3°C / min, and cool to room temperature to obtain a fiber preform II.

6. The method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material according to claim 1, characterized in that: In step 400, the thickness of the outer dense layer of the second fiber preform accounts for 1 / 5 to 1 / 2 of the total thickness of the second fiber preform, and the ceramic content is 20 to 50 vol.%.

7. The method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material according to claim 1, characterized in that: In step 500, the precursor solution is any one of a diboride precursor, a silicon carbide precursor or a silicon boron nitrogen precursor; The pressure of immersion in the precursor solution is 4-9 MPa, the immersion temperature is 45-60° C., and the solid content of the precursor solution is 30-50%; The ceramic heating rate in the vacuum sintering furnace is 4~10℃ / min, and the cracking temperature is 1000~1500℃; The protective atmosphere is any one of argon and helium; In step 500, the ceramic content of the outer dense layer of the composite body 3 is 50-80 vol.%, and the ceramic content of the inner loose layer is 20-30 vol.%.

8. The method for preparing a fiber-reinforced functional gradient layered ceramic matrix composite material according to claim 1, characterized in that: In step 600, during the hot pressing treatment, the temperature is 1000-1500°C, the heating rate is 1-2°C / min, the pressure is 10-50MPa, and the heat preservation is finally performed for 0.5-1h; The thickness of the fiber-reinforced functional gradient layered ceramic matrix composite material is 1 / 4 to 1 / 2 of the thickness of the fiber preform.

9. A fiber-reinforced functional gradient layered ceramic matrix composite material, characterized in that: The fiber-reinforced functional gradient layered ceramic matrix composite material is prepared using the fiber-reinforced functional gradient layered ceramic matrix composite material preparation method as described in any one of claims 1-8, the thickness of the fiber-reinforced functional gradient layered ceramic matrix composite material is 1 / 4 to 1 / 2 of the thickness of the fiber preform, the fiber-reinforced functional gradient layered ceramic matrix composite material comprises an outer dense layer and an inner loose layer, the ceramic content of the outer dense layer is 60 to 90 vol.%, and the ceramic content of the inner loose layer is 30 to 40 vol.%.

Citation Information

Patent Citations

  • Automatic charging device for overflowing vacuum freezing / drying machine

    CN202171384U